2012
DOI: 10.1080/10407782.2012.691059
|View full text |Cite
|
Sign up to set email alerts
|

Entropy Generation During Natural Convection in a Porous Cavity: Effect of Thermal Boundary Conditions

Abstract: Entropy generation plays a significant role in the overall efficiency of a given system, and a judicious choice of optimal boundary conditions can be made based on a knowledge of entropy generation. Five different boundary conditions are considered and their effect of the permeability of the porous medium, heat transfer regime (conduction and convection) on entropy generation due to heat transfer, and fluid friction irreversibilities are investigated in detail for molten metals (Pr ¼ 0.026) and aqueous solutio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
19
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(20 citation statements)
references
References 47 publications
1
19
0
Order By: Relevance
“…A fair number of studies on entropy generation during natural convection process in closed cavities filled with fluid and porous medium were carried out in last few years [20][21][22][23][24][25][26][27][28][29][30][31]. Mahapatra et al [20] studied entropy generation analysis in a square enclosure filled with air in presence of adiabatic and isothermal blocks.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A fair number of studies on entropy generation during natural convection process in closed cavities filled with fluid and porous medium were carried out in last few years [20][21][22][23][24][25][26][27][28][29][30][31]. Mahapatra et al [20] studied entropy generation analysis in a square enclosure filled with air in presence of adiabatic and isothermal blocks.…”
Section: Introductionmentioning
confidence: 99%
“…A detailed analysis on entropy generation due to buoyancy driven flow in discretely heated porous square cavities was done by Kaluri and Basak [27]. Further, Basak et al [28] performed entropy generation analysis in porous square cavities with various thermal boundary conditions. Anandalakshmi and Basak [29] showed the effect of inclination angle on entropy generation in a porous rhombic cavity and compared the results with square cavity.…”
Section: Introductionmentioning
confidence: 99%
“…In their report, they stated that entropy generation increases with an increase in magnetic parameter. Other studies on the analysis of entropy generation in various fluid flows can be found in [1,5,6,8,13,20,28].…”
Section: Introductionmentioning
confidence: 99%
“…Analyses of the second law of thermodynamics are also focused on saturated porous cavities, as in Baytas [8], Al-Hadhrami et al [9], Mahmud and Fraser [10], Hooman and Ejlali [11], Zahmatkesh [12], Varol et al [13], and Basak et al [14].…”
Section: Introductionmentioning
confidence: 99%